A Probabilistic Protocol for Multihop Routing in VANETs. (18th August 2010) - Fukuyama, Junichiro
Abstract : Vehicular ad hoc networks (VANETs) allow communications over sequences of vehicles with radio devices. There are many possible applications over a VANET such as traffic jam warning, collision warning, parking lot reservations, camera picture feed, and so forth. There have been quite a few results in the area seeking for a fast and reliable communication protocol due to their potential. VANETs, however, are pointed out as difficult for numerical optimizations due to frequent changes in their topologies. As a result, heuristic methods such as GPSR have been mainly used for routing packets over multihop communications. In this paper, we present an algorithm to precompute the probability that communication is possible between specified source and destination in a VANET, under certain mathematical assumption. The proposed new protocol for multihop communication refers to a lookup table containing the precomputed data to decide a good packet forwarder quickly. We create a simulation testbed that seems challenging for all the existing multihop routing protocols for VANETs, in which we test ours. We see much improved performances over GPSR after the algorithm is refined for some practical issues.